Finding the Optimal Pose of 2D LLT Sensors to Improve Object Pose Estimation - Heczko, Dominik; Oščádal, Petr; Kot, Tomáš; Boleslavský, Adam; Krys, Václav; Bém, Jan; Virgala, Ivan; Bobovský, Zdenko (Sensors (Basel, Switzerland), 2022)
In this paper, we examine a method for improving pose estimation by correctly positioning the sensors relative to the scanned object. Three objects made of different materials and using different manufacturing technologies were selected for the experiment. To collect input data for orientation estimation, a simulation environment was created where each object was scanned at different poses. A simulation model of the laser line triangulation sensor was created for scanning, and the optical surface properties of the scanned objects were set to simulate real scanning conditions. The simulation was verified on a real system using the UR10e robot to rotate and move the object. The presented results show that the simulation matches the real measurements and that the appropriate placement of the sensors has improved the orientation estimation.
Keywords: optimal pose; ICP algorithm; optimal configuration; laser scanning; algoritmy; Lasers; Algorithms; virtual scanning; pose estimation; Computer Simulation; lasery; orientation estimation; LLT sensor; počítačová simulace